2021
DOI: 10.2147/ppa.s303822
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-National Survey of People Living with Hemophilia: Impact on Daily Living and Patient Education in Central Europe

Abstract: Background Information about the impact of hemophilia on daily living and information preferences for patients and their caregivers in Central Europe has been limited. Methods This cross-national survey was conducted between April 1 and October 15, 2020 and utilized a self-administered questionnaire to collect data (Typeform™) from people living with hemophilia in Bulgaria, Croatia, Czech Republic, Hungary, Slovakia and Slovenia. The questionnaire included 22 questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…More than half of the respondents was satisfied with the care received. Similar results were obtained in cross-national survey covering Central Europe [16]. Over 70% of patients with haemophilia or their caregivers were satisfied with their level of knowledge about the disease.…”
Section: Education Of Patientssupporting
confidence: 82%
“…More than half of the respondents was satisfied with the care received. Similar results were obtained in cross-national survey covering Central Europe [16]. Over 70% of patients with haemophilia or their caregivers were satisfied with their level of knowledge about the disease.…”
Section: Education Of Patientssupporting
confidence: 82%
“… 30 Moreover, it has highlighted the role of behavioral precautions, the uncertainty of actions, and the fear of unexpected bleeding on depression, frustration, isolation, and embarrassment. 31 Other studies confirmed some aspects related to comorbidities (arthropathy, HCV/HBV/HIV co-infections, liver cirrhosis due to HBV/HCV infections, and coexisting heart and kidney diseases, for example) are ongoing challenges that block the accepting health status in these persons. 32 , 33 As experienced in our sample, the correlation between the perceived quality of life and the adopted lifestyle further corroborates this point.…”
Section: Discussionmentioning
confidence: 90%
“…Se empleó cuestionarios auto administrados en línea mediante la herramienta Typeform, que ha manifestado fiabilidad apta para ser utilizada en estudios transnacionales europeos durante el levantamiento de información (Banchev et al, 2021). Se incluyó escalas Likert de autoinforme, que son una parte esencial de la psicología moderna para evaluar los aspectos psicométricos que comprenden este estudio (Jebb et al, 2021).…”
Section: Metodologíaunclassified